Validation of the Chinese version of the resilience scale for the oldest-old - Wang, Ning; Chen, Hongyu; Zhang, Minyi; Wang, Yuanyuan; Xue, Zhihan; Hao, Xixi; Liu, Yan (Frontiers in Psychology, 2023)
Background Resilience is one of the most important variables associated with adaptive ability. The resilience scale for the oldest-old age (RSO) has been designed to measure the resilience among the oldest-old people. Originally developed in Japan, this scale has not been used in China. The objective of this study was to translate the RSO into Chinese and investigate its validity and reliability among the community’s oldest-old adults aged ≥80 years. Methods A total of 473 oldest-old people who came from communities were recruited by convenience sampling for the assessment of construct validity using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). In addition, internal consistency reliability, test–retest reliability, face validity, and content validity were used to evaluate the psychometric characteristics of RSO. Results The RSO demonstrated good face validity and content validity. The content validity index of the Chinese version of the RSO was 0.890. Moreover, one factor was extracted by exploratory factor analysis, which accounted for 61.26% of the variance. The RSO had high internal consistency with a Cronbach’s alpha = 0.927. The test–retest reliability was 0.785. The item-total correlations ranged from 0.752 to 0.832. Conclusion The results of the study indicate that the Chinese version of the RSO questionnaire has good reliability and validity and can be recommended for use by health and social service agencies as a method for assessing the resilience of the oldest-old in the community.